Anatomy of the lumbar interspinous ligament: findings relevant to epidural insertion using loss of resistance. Issue 12 (22nd October 2021) - Lawrence, Sue; Llewellyn, Stacey; Hunt, Helen; Cowin, Gary; Sturgess, David J; Reutens, David
Abstract : Background and objectives: The 'loss of resistance' technique is used to determine entry into the epidural space, often by a midline needle in the interspinous ligament before the ligamentum flavum. Anatomical explanations for loss of resistance without entry into the epidural space are lacking. This investigation aimed to improve morphometric characterization of the lumbar interspinous ligament by observation and measurement at dissection and from MRI. Methods: Measurements were made on 14 embalmed donor lumbar spines (T12 to S1) imaged with MRI and then dissected along a tilted axial plane aligned with the lumbar interspace. Results: In 73 interspaces, median (IQR) lumbar interspinous plus supraspinous ligament length was 29.7 mm (25.5–33.4). Posterior width was 9.2 mm (7.7, 11.9), with narrowing in the middle (4.5 mm (3.0, 6.8)) and an anterior width of 7.3 mm (5.7, 9.8). Fat-filled gaps were present within 55 (75%). Of 51 anterior gaps, 49 (67%) were related to the ligamenta flava junction. Median (IQR) gap length and width were 3.5 mm (2.5, 5.1) and 1.1 mm (0.9, 1.7). Detection of gaps with MRI had 100% sensitivity (95% CI 93.5 to 100), 94.4% specificity (72.7, 99.9), 98.2% (90.4, 100) positive predictive value and 100% (80.5, 100) negative predictive value against dissection as the gold standard. Conclusions: The lumbar interspinous ligament plus supraspinous ligament are biconcave axially. It commonly has fat-filled gaps, particularly anteriorly. These anatomical features may form the anatomical basis for false or equivocal loss of resistance.